The Public Service Commission of the State of Kedah Darul Aman / Azrin Izzat Abdul Bari - Abdul Bari, Azrin Izzat (Universiti Teknologi MARA, Perlis, 2024)
The Public Service Commission of the State of Kedah Darul Aman was established by the Kedah State Legislative Assembly on August 24, 1959, under the "State Public Service Commission Enactment 1959" or the State Public Service Commission Act 1959. The enactment received the consent of His Royal Highness the Sultan of Kedah on October 20, 1959, and was subsequently gazetted on October 29, 1959. According to the enactment, the Kedah State Public Service Commission is responsible in several processes which are recruitment, termination, disciplinary action, promotion, and pension. This internship report is highlighting the overview of the human resources process that I have been experienced especially from the recruitment perspective.